The falcon [large type] - Maldonado, Isabella, 1965- (Maldonado, Isabella, 1965- FBI agent Nina Guerrera series, 2024)
"Six female undergrads at an elite university vanish. The media descends. The families demand action. And as Special Agent Nina Guerrera follows clue by chilling clue, she realizes she's tracking the most cunning predator of her career. The case takes a turn for the worse, and the bizarre, when several victims are found perfectly preserved. No signs of violence, no hint of how they died. Just more evidence that the killer is cruel, calculating, and a master of mind control. With her mission compromised, Nina must face her greatest failure--and greatest fear--to stop a deadly hunter before he claims another prize" --